Serological screening of the Schistosoma mansoni adult worm proteome. - Fernanda Ludolf; Paola R Patrocínio; Rodrigo Corrêa-Oliveira; Andréa Gazzinelli; Franco H Falcone; André Teixeira-Ferreira; Jonas Perales; Guilherme C Oliveira; Rosiane A Silva-Pereira (Public Library of Science (PLoS), 2014)
BACKGROUND: New interventions tools are a priority for schistosomiasis control and elimination, as the disease is still highly prevalent. The identification of proteins associated with active infection and protective immune response may constitute the basis for the development of a successful vaccine and could also indicate new diagnostic candidates. In this context, post-genomic technologies have been progressing, resulting in a more rational discovery of new biomarkers of resistance and antigens for diagnosis. METHODOLOGY/PRINCIPAL FINDINGS: Two-dimensional electrophoresed Schistosoma mansoni adult worm protein extracts were probed with pooled sera of infected and non-infected (naturally resistant) individuals from a S. mansoni endemic area. A total of 47 different immunoreactive proteins were identified by mass spectrometry. Although the different pooled sera shared most of the immunoreactive protein spots, nine protein spots reacted exclusively with the serum pool of infected individuals, which correspond to annexin, major egg antigen, troponin T, filamin, disulphide-isomerase ER-60 precursor, actin and reticulocalbin. One protein spot, corresponding to eukaryotic translation elongation factor, reacted exclusively with the pooled sera of non-infected individuals living in the endemic area. Western blotting of two selected recombinant proteins, major egg antigen and hemoglobinase, showed a similar recognition pattern of that of the native protein. CONCLUDING/SIGNIFICANCE: Using a serological proteome analysis, a group of antigens related to the different infection status of the endemic area residents was identified and may be related to susceptibility or resistance to infection.